ANTISEPTICS OF NATURAL, NON-CHEMICAL ORIGIN, THEIR TOXICOLOGICAL AND ALLERGIC EFFECTS ON THE BODY OF LABORATORY ANIMALS - Kadralieva, B. T.; Nametov, A. M.; Murzabaev, K. E.; Dushaeva, L. Zh.; Karagulov, A. I.; Orynkhanov, K. A.; Marat, M. B. (ЗКАТУ им. Жангир хана, 2025)
In modern practical disinfectology, It is argued that ideal chemical agents, high disinfecting activity, and some other properties should be characterized by ecological safety, minimum toxicity and environmental safety. Environmental protection minimizes toxic effects on humans and animals, ease of utilization of spent solution. Antiseptics of natural, nonchemical origin are of great importance to solve this. Origin Spilled neutral concentrated anolyte (ANK), Ozone (O3), Shungite carbon and Propolis. These antiseptics of natural origin are environmentally friendly and have bactericidal and fungicidal action. They can be used for disinfection and disinfection of objects in medical and veterinary facilities. Our research aimed to determine the toxicological and allergic properties of anolyte, ozone, shungite, propolis, and their complexes shungite+ozone+anolite. "Shozan", propolis+ozone+anolite "Prozan", and shungite+propolis+ozone+anolite "Shuprozan" on laboratory animals. 1. According to the research results, antiseptics of natural origin and their complexes at single intraperitoneal injection at a dose of 1 ml do not have a toxic effect on laboratory mice. Laboratory mice Do not have an allergic effect on the cornea and conjunctival mucosa of the eye. Skin-resorptive reactions do not have an allergic effect on the skin. Essential antiseptics ethanol in a solution of 20% and hydrogen peroxide in a solution concentration of 1% have a toxic effect at a single intraperitoneal injection at a dose of 1 ml on laboratory mice and cause their death. It has an allergic effect on the cornea and mucosa conjunctiva of the eye, determining the skin-resorptive reaction has an allergic effect on the skin of rabbits.
Аntiseptics of natural, non-chemical origin, their toxicological and allergic effects on the body of laboratory animals / B. T. Kadralieva, A. M. Nametov, K. E. Murzabaev, L. Zh. Dushaeva, A. I. Karagulov, K. A. Orynkhanov, M. B. Marat . - Текст : непосредственный // "Ғылым, зерттеулер, білім: даму тенденциялары" атты XXV халықаралық ғылыми-практ. конф. жинағы = Сollected papers XXV International scientific and practical conference "Science, research, education: development trends"= «Наука, исследования, образование: тенденции развития»: cб. XXV междунар. науч.-практ. конф. - Орал: Жәңгір хан атындағы БҚАТУ. - 2025. - Р. 54-63 (Uralsk).
Keywords: ANK anolyte; ozone (O3); shungite carbon; propolis; ethanol; hydrogen peroxide toxicological and allergic properties; БҚАТУ; ғылыми журнал